Dupuytren's disease - Richard Trèves (PAGEPress Publications, 2011)
Dupuytren's disease is a contracture of the hand derived from the retractile fibrosis of the palmar aponeurosis, that leads to a progressive deformity in flexion of fingers. It has been named from the French surgeon Guillaume Dupuytren (1777-1835), that described it in 1831. In this note it is sketched a short biography of Dupuytren and the main clinical features of the disease are described, underlining some particular aspects of therapy.